Charter and Ordinances of the City of Olympia: Also General Laws of Washington Territory, Relative to the Government of Incorporated Cities and Towns, at 80, Ordinance No. 152, § 4 (1886) - (:unkn) unknown (My University, 1886)
Any person who shall, within the following limits, to wit: between Union street on the south-east corner of Cherry; thence north, on a line, to First street: thence west to the western shore of Budd's inlet; thence south to the line of Union street, continued; fire off or discharge any gun, pistol or firearm of any kind, shall be liable to a fine of not less than five nor more than twenty dollars, or by imprisonment for not less than five nor more than ten days, or by both such fine and imprisonment.
Keywords: DISCHARGE